Dietary patterns and indicators of cardiometabolic risk among rural adolescents: A cross-sectional study at 15-year follow-up of the MINIMat cohort - Islam, Mohammad Redwanul; Rahman, Syed Moshfiqur; Selling, Katarina; Näsänen-Gilmore, Pieta; Kippler, Maria; Kajantie, Eero; Rahman, Anisur; Pervin, Jesmin; Ekström, Eva-Charlotte (Frontiers in Nutrition, 2023)
Background: Diet being a modifiable factor, its relationship with cardiometabolic risk is of public health interest. The vast majority of studies on associations of dietary patterns with cardiometabolic risk indicators among adolescents are from high-income countries and urban settings. We sought to describe dietary patterns and examine their associations with selected cardiometabolic risk indicators – waist circumference (WC), systolic blood pressure, fasting lipid profile and insulin resistance – along with its gender stratification among adolescents in a low-income, rural setting. Methods: This cross-sectional study utilized data from the 15-year follow-up of the Maternal and Infant Nutrition Interventions in Matlab (MINIMat) cohort in southeast Bangladesh. We employed a single, qualitative 24-hour recall to assess diet. Dietary patterns were derived from simple K-means cluster analysis, and calculation of dietary diversity score (DDS) using a validated instrument. Anthropometric parameters and systolic blood pressure were recorded. Fasting plasma triglyceride, total cholesterol, low- and high-density lipoproteins, insulin and glucose levels were measured. We calculated insulin resistance using the Homeostasis Model Assessment equation (HOMA-IR). Three right-skewed outcome variables were natural log (Ln) transformed: WC, triglyceride and HOMA-IR. Omnibus and gender-specific multiple linear regression models were fitted. Results: Among 2253 adolescents (52.1% girls, 7.1% overweight/obese), we identified four diet clusters: Traditional, Fish-dominant, Meat-dominant and High-variety. No significant associations were found between the clusters and indicators. On gender-stratification, triglyceride levels were lower among boys in the Fish-dominant (Ln-triglyceride βadjusted: –0.09; 95% confidence interval (CI): –0.15, –0.02) and Meat-dominant (Ln-triglyceride βadjusted: –0.08; 95% CI: –0.15, –0.004) clusters than among boys in the Traditional cluster. Compared to boys in the bottom quartile of DDS, boys in the top quartile had 2.1 mm of Hg (95% CI: 0.5, 3.6) higher systolic blood pressure and 1.9% (95% CI: 0.01–3.8%) higher WC. Conclusion: While statistically significant, the gender-specific differences in triglyceride, systolic blood pressure and waist circumference across dietary patterns were small. Associations between dietary patterns and cardiometabolic risk indicators may require a time lag beyond mid-adolescence to manifest in a rural setting. Prospective studies are warranted to delineate the magnitude and direction of those associations.